Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Keuangan BUMN dengan Ukuran Perusahaan sebagai Variabel Kontrol - Tusianto Dwi Sapto Aji; Ika Wulandari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to determine the effects of the Board of Directors, Board of Commissioners, Audit Committee, and Company Size on the financial performance of state-owned enterprises (SOEs). The sample was selected using purposive sampling, resulting in 26 companies meeting this study's criteria, with a total of 78 data points. The analysis techniques used were Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Test, Hypothesis Testing, and Correlation Test. The results indicate that the Board of Directors has a significant positive effect on the financial performance of SOEs, as do the Board of Commissioners, Audit Committee, and Company Size. This means that the greater the number of independent variables, the higher the quality of the financial reports produced, which will be accompanied by increased company performance and will create a good network with parties outside the company.